PENGARUH AGRESIVITAS PAJAK, MEDIA EXPOSURE DAN GENDER DIVERSITY TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Septi Damayanti, (2021)
This study aims to determine the relationship between tax aggressiveness, media exposure and gender diversity on the disclosure of corporate social responsibility in manufacturing and natural resource companies (mining and agriculture) listed on the Indonesia Stock Exchange in 2017-2019. Using multiple linear regression with quantitative methods and secondary data on 26 companies. Researchers detect CSR disclosure by measuring GRI Standards and GRI G4, tax aggressiveness by book tax difference (BTD), media exposure by the amount of media/coverage, gender diversity by the proportion of female commissioners. Researchers found contradictory results, that tax aggressiveness and media exposure have no effect on CSR disclosure. On the other hand, the researchers also found that gender diversity had a negative effect on CSR disclosure. Furthermore, future researchers are expected to be able to uncover each component of CSR disclosure, especially by publishing a company sustainability report.